Model-Based PAT for Quality Management in Pharmaceuticals Freeze-Drying: State of the Art - Fissore, Davide (Frontiers in Bioengineering and Biotechnology, 2017)
Model-based Process Analytical Technologies can be used for the in-line control and optimization of a pharmaceuticals freeze-drying process, as well as for the off-line design of the process, i.e. the identification of the optimal operating conditions. This paper aims presenting the state of the art in this field, focusing, particularly, on three groups of systems, namely those based on the temperature measurement (i.e. the soft-sensor), on the chamber pressure measurement (i.e. the systems based on the test of pressure rise and of pressure decrease), and on the sublimation flux estimate (i.e. the TDLAS and the valveless monitoring system). The application of these systems for in-line process optimization (e.g. using a Model Predictive Control algorithm) and to get a true Quality-by-Design (e.g. through the off-line calculation of the design space of the process) is presented and discussed.